The Diagnostic Pitfalls and Clinical Challenges of Unilateral Facial Paralysis in Acute Demyelinating Disorders: A Case Report and Literature Review - Alhowaish, Thamer S.; Alqahtani, Hossam Ali; Alhamadh, Moustafa S.; Alanazi, Ali (Case reports in neurological medicine, 2025)
Guillain–Barré syndrome (GBS) is an acute immune‐mediated polyradiculoneuropathy typically presenting with progressive limb weakness and areflexia, while bilateral facial nerve involvement is a well‐recognized feature. However, unilateral facial palsy is exceedingly rare and can closely mimic Bell’s palsy, complicating early diagnosis. We report the case of a previously healthy 32‐year‐old man whose illness began with subtle bilateral fingertip numbness ascending to his elbows, followed by the acute onset of right‐sided facial weakness, perioral numbness, slurred speech, and inability to close his right eye. These symptoms developed shortly after an upper respiratory tract infection and were soon accompanied by toe numbness and gait unsteadiness. Examination revealed isolated right lower motor neuron facial palsy and a rapid progression from diminished to absent deep tendon reflexes, while muscle strength and general sensation remained preserved. The diagnosis of GBS was confirmed by absent reflexes, albuminocytologic dissociation in cerebrospinal fluid, and electrodiagnostic evidence of bilateral facial and trigeminal neuropathy. The patient was treated successfully with intravenous immunoglobulin, resulting in significant clinical improvement. This case underscores the diagnostic challenges of atypical GBS presentations and highlights the importance of considering GBS in patients with acute, evolving cranial neuropathies, even when the presentation closely resembles more common conditions such as Bell’s palsy.